PELATIHAN PEMBUATAN PROPOSAL PENELITIAN TINDAKAN KELAS PADA GURU-GURU SMP NEGERI 2 TONDANO - Mike Mumekh (LPPM UNIMA, 2021)
Based on the results of field observations of the many problems in this activity, how to improve the skills of teachers regarding the preparation of CAR proposals. The teacher's lack of ability in preparing CAR proposals is caused, among other things, by the teacher's lack of knowledge and understanding of classroom action research. The purpose of this training activity is to improve the skills of teachers in preparing classroom action research proposals. The target audiences in this service are all teachers at SMA Negeri 2 Tondano who have the potential to be fostered and developed their abilities in preparing classroom action research proposals. Based on the results of the activity evaluation, it can be concluded that this training has a positive impact and opens the participants' insight to be able to improve their mastery of soccer skills.